1983
DOI: 10.1007/bf00526523
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biological monitoring among stainless steel welders

Abstract: Ten manual metal arc (MMA) high alloy stainless steel (SS) welders were studied during one week and the concentrations of chromium (Cr) and nickel (Ni) were determined in their urine and blood. Stationary and personal air samples were collected from the immediate work environment; they covered the entire work period. Spot urine samples were collected during the follow-up period. Whole blood and plasma samples were taken from the workers before and after one shift, and the retention rate of magnetic dust in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This was determined from regression lines y = kx + k. Participation ofparticular Cr forms in relation to total Cr was determined in the same way ( fig 6, table 4). The relations presented indicate that participation of particular Cr forms compared with total Cr content in all samples determined (samples exceeding the sensitivity of the method) was similar (table 4) Our studies, performed in detail for the first time in Polish industry, indicated that the TWA (8 Also, the presence of some other processes applied in the vicinity affects the chemical composition of the background: under certain conditions, the background may significantly affect the fumes collected in the breathing zone, although usually the background concentration of fumes measured with stationary samplers constitutes about one tenth of that found in the breathing zone.6 17 Relations exist between concentrations of elements in fumes and distance from the welding area. The results of our studies indicate that MMA/SS fumes and their elements are usually more concentrated in Table 2 the breathing zone than in the workplaces.…”
Section: Glass Fibre Filtermentioning
confidence: 54%
“…This was determined from regression lines y = kx + k. Participation ofparticular Cr forms in relation to total Cr was determined in the same way ( fig 6, table 4). The relations presented indicate that participation of particular Cr forms compared with total Cr content in all samples determined (samples exceeding the sensitivity of the method) was similar (table 4) Our studies, performed in detail for the first time in Polish industry, indicated that the TWA (8 Also, the presence of some other processes applied in the vicinity affects the chemical composition of the background: under certain conditions, the background may significantly affect the fumes collected in the breathing zone, although usually the background concentration of fumes measured with stationary samplers constitutes about one tenth of that found in the breathing zone.6 17 Relations exist between concentrations of elements in fumes and distance from the welding area. The results of our studies indicate that MMA/SS fumes and their elements are usually more concentrated in Table 2 the breathing zone than in the workplaces.…”
Section: Glass Fibre Filtermentioning
confidence: 54%
“…To assess the Cr exposure and uptake, biological monitoring has been used in addition to air monitoring and since 1960s, urinary Cr has been considered as a valid indicator of recent Cr exposure (Linderberg and Vesterberg 1983;Rahkonen et al 1983;Welinder et al 1983;McAughey et al 1988;IARC 1990). In total Cr exposure due to air, the DE subjects show 0.101 ± 0.003 mg/m 3 , which was higher compared to IE subjects and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirms the earlier reports that the biological levels of chromium (in urine and blood) are good indicators of the exposure level of chromium at the work place. [2830] Thus, air and biological monitoring can effectively be used for assessing the external and internal exposure to chromium and associated health risks among the exposed human population in epidemiological health surveys. [20]…”
Section: Discussionmentioning
confidence: 99%